Managing Leader Selection in European Political Parties
XVI, 254 p. 4 illus.
Keywords: This book explores the varying ways in which political parties in Europe make arguably their most important decisions: the selection of their leaders. The choice shapes the representation of a party externally. It also influences the management of internal conflict, because there will always be some disagreement about the party’s direction. The rules of selection will naturally affect the outcome. Yet there is more to it than rules. Sometimes the process is open and fiercely contested. Sometimes the field of potential leaders is filtered even before the decision reaches the selectorate – the organ that, according to party statutes, formally makes the appointment. The selectorate might have only a single candidate to ratify, a so-called ‘coronation’. The book presents a framework for analysing both the formal and informal sides of leader selection, and hones the framework through its application in a series of case studies from nine European countries. Nicholas Aylott is Associate Professor of Political Science at Södertörn University, Sweden. He specialises in comparative politics, with a particular focus on political parties. He is co-author of Parties in Multi-Level Polities: The Nordic Countries Compared (2013) and has published in such journals as the European Journal of Political Research and Party Politics. Niklas Bolin is Associate Professor of Political Science at Mid Sweden University, Sweden. His main research interests are parties and elections, particularly organisation, leadership, intra-party democracy, radical right parties and green parties. He has published in journals including Party Politics, Scandinavian Political Studies and West European Politics.